1969
DOI: 10.1002/macp.1969.021280122
|View full text |Cite
|
Sign up to set email alerts
|

Note on the effect of γ‐irradiation on the melting behavior of polyethylene single crystals

Abstract: Polyethylene single crystals were prepared from isoamyl acetate solutions, whose thickness was 200 A. They melted without significant reorganization during the heating process

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1970
1970
1997
1997

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 16 publications
(3 reference statements)
0
16
0
Order By: Relevance
“…This G-value would represent only the upper limit since the decrease in 2ff/~ is caused not only by the increase in lattice enthalpy, but also by a decrease in entropy of melt due to cross-linking [30]. However, even this overestimate is substantially lower than the overal G-value of 1.5 reported for PE at moderate irradiation doses [97].…”
Section: Salovey and Kellermentioning
confidence: 60%
“…This G-value would represent only the upper limit since the decrease in 2ff/~ is caused not only by the increase in lattice enthalpy, but also by a decrease in entropy of melt due to cross-linking [30]. However, even this overestimate is substantially lower than the overal G-value of 1.5 reported for PE at moderate irradiation doses [97].…”
Section: Salovey and Kellermentioning
confidence: 60%
“…The crystals of C 160 and Cl20 from IAAC were like tree leaves, and similar to the extended chain crystals which Takamizawa et at. 10 obtained previously from low molecular weight PE fractions. Toda 11 and Frank 12 reported that roundshaped PE crystals were obtaind from solution crystallized at high temperature, and discussed the mechanism of crystallization.…”
Section: Measurementsmentioning
confidence: 99%
“…With the standard heating rate of 0.5 K min -1 , the endothermic peak of once-folded chain crystal became ambiguous, which suggests that stabilization from a metastable state of once-folded chain crystal to the extended chain crystal gradually occurs at such a slow heating rate. From this point of view, cross-linking experiment 14 for amorphous parts was made by y-ray irradiation for the purpose of inhibiting melt-recrystallization. However, this experiment was unsuccessful for C160 and C120 crystals due to the absence ofa double bonds in the parts to be crosslinked.…”
Section: Polymorphism Of Melting Process For Once-foldedmentioning
confidence: 99%
“…This crystal, having a lamellar thickness of 180A, melted without reorganization at ordinary pressure and its melting temperature could be given by the intersection temperature. 23 The DTA curve at low pressure below 1.5 kbar shows a sharp, single melting peak. With increase in pressure a shoulder appears, and then the peak becomes a doublet.…”
Section: Dt a And Melting Temperature Of Folded-chainmentioning
confidence: 99%
“…3, 1975 tained at atmospheric pressure on solution-grown crystals: thick crystals gave single peak, whereas thin ones showed a multiple peak. 23 If this interpretation is correct, the higher two peaks of the three can be assigned to the melting of crystallites with different degrees of perfection formed on the heating process. There is, however, a possibility that they correlate with an appearance of the high-pressure phase proposed by Bassett and Turner 26 ' 27 and by Takemura and coworkers.…”
Section: Dt a And Melting Temperature Of Folded-chainmentioning
confidence: 99%